On designing an active tail for legged robots: simplifying control via decoupling of control objectives. Issue 3 (16th May 2016) - Heim, Steve W.; Ajallooeian, Mostafa; Eckert, Peter; Vespignani, Massimo; Ijspeert, Auke Jan
Abstract : Purpose: The purpose of this paper is to explore the possible roles of active tails for steady-state legged locomotion, focusing on a design principle which simplifies control by decoupling different control objectives. Design/methodology/approach: A series of simple models are proposed which capture the dynamics of an idealized running system with an active tail. These models suggest that the overall control problem can be simplified and effectively decoupled via a proper tail design. This design principle is further explored in simulation using trajectory optimization. The results are then validated in hardware using a one degree-of-freedom active tail mounted on the quadruped robot Cheetah-Cub. Findings: The results of this paper show that an active tail can greatly improve both forward velocity and reduce body-pitch per stride while adding minimal complexity. Further, the results validate the design principle of using long, light tails compared to shorter heavier ones. Originality/value: This paper builds on previous results, with a new focus on steady-state locomotion and in particular deals directly with stance phase dynamics. A novel design principle for tails is proposed and validated.